Ekoteologi Arkipelagis: Sebuah Ekoteologi dari Keseharian Indigenous Indonesia - Maggang, Elia (Asosiasi Teolog Indonesia, 2025)
The dominance of the green depicting Eurocentric, land-based colonial perspectives within the subfield of ecotheology has led to the neglect of crises affecting the sea. In response, blue ecotheology reflects a growing emphasis on marine and coastal communities within ecotheological discourse. Yet blue ecotheology has not adequately addressed the crucial issue of interconnectedness between land and sea communities, an entanglement pivotal for both causing and resolving ecological crises at sea. Therefore, this article proposes archipelagic ecotheology as a framework to elevate blue perspectives and simultaneously articulate a vision of interconnectedness between sea (blue) and land (green) communities as a unified planetary entity. This ecotheology draws inspiration from Indigenous Indonesian archipelagic everyday life, encapsulated in sayings such as that from Pantar Island: “tei kari dekang, sera bata ra’ung” (yams come down from the mountains, fish come up from the sea). Navigating archipelagic everydayness, I read the narrative of Jesus feeding the multitude with fish and loaves in Mark 6:30-44 from what will be defined as an ecopneumatological perspective, to construct an archipelagic ecotheology that begins with and aims for the living interactions between sea and land communities. This archipelagic ecotheology may serve as a model for ecotheological discourse that embraces the diverse ecological communities of our planet.